FACULTY OF TEACHER TRAINING AND EDUCATION STUDENTS` READING HABIT: A CASE STUDY IN UNIVERSITY OF BATURAJA - Yentri Anggeraini (ELTE Journal (English Languange Teaching and Education), 2016)
ABSTRACTThe objective of this study were to find out (1) reading habit of the second semester students in Faculty of Teacher Training and Education, University of Baturaja, (2) what the students read when they connect to the internet. The population were all of students in Faculty of Teacher Training and Education with the total 1963 students. The samples of this study taken by random sampling based on the confidence level 90 or 99 percent were 351 respondents. The data were collected in form of questionnaire and interview and was analyzed by using percentage analysis. This study had proved that although most of the students were motivated to read various kinds of texts, their reading practices are mostly because of doing reading assignments, passing the exam, and getting a job. Still, only few of them read for pleasure and for happiness which could be assumed as an indicator of good reading habits.  The activities of the students when they connect to the internet were: downloading texts, reading e-book, chatting with friends in social media, reading messages in social media account, reading e-journal, checking and read email, downloading software, and playing online games. Secondly, the students visit the library for specific study purposes, such as preparing notes or findings answers to questions, preparing for thesis consultation, borrowing books, photocopying, and reading research proposal, thesis, and waiting for the next class.  Keywords: Reading, reading habit